The Effect Addition Of Viterna Plus Supplement With Different Doses On Feed Towards GrowthAnd Survival Rate Of Vannamei Shirmp (Litopenaeus vannamei) with Recirculation System - Adilla, Deane Marza; Rusliadi, Rusliadi; Mulyadi, Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This aims ofthe research was to find out the optimal dose of viternasupplement to increase the growth and survival of Vannamei shrimp (Litopaneaus vannamei) with recirculation systems. This research was carried out for 40 days in May - June 2019 held at Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The design of this research is an experimental model using Completely Randomize Design Factorial pattern (RAL) of 1 factor, 5 treatment levels and 3 replications. The treatment level of this study was P0 (feed without the addition of viterna), P1 (addition of viterna 5 ml / kg of feed), P2 (addition of viterna 10 ml / kg of feed), P3 (addition of viterna 15 ml / kg of feed),P4(addition of viterna 20 ml / kg of feed). The best treatment is the treatment of (P3) additional viterna doses of 15 ml / kg of feed resulting in absolute weight growth of 1,412 g, specific growth recorded of 7,883%, feed efficiency 80,43% and survival rate of 98,33%. Water quality during the study was temperature ranging from 28-30oC, pH ranged from 7.4-7,8, dissolved oxygen (DO) ranged from 4,5 to 5,8 mg / L, and ammonia (NH3) ranged from 0.0057-0, 0096 mg / L. Keywords:Doses,Viterna, Growth,Vannamei shirmp.